Does the Village Fund in The Middle of Pandemic COVID-19 Still Accountable and Transparent? - Miranda Hutapea; Aprina Hapsari (Politeknik Negeri Madiun, 2021)
This study aims to describe the practice of accountability and transparency in managing village funds, especially concerning the allocation of village funds for direct cash assistance during the COVID-19 pandemic. This research is a qualitative descriptive study. This study's data are primary data obtained through in-depth interviews with village heads, village secretaries, village consultative bodies, and village community representatives. The results showed that the implementation of the principle of horizontal, vertical accountability and transparency had been manifested in the management of village funds in Village X. Except for the regulation of horizontal accountability at reporting and administration stages and the principle of transparency in implementation. This is due to weak human resources and not a maximal risk assessment. The village government needs to improve the principles of accountability and transparency, especially in the implementation, reporting, administration, and improvement of good governance, to meet all its stakeholders' satisfaction.